The use of a wireless network to provide real-time augmented feedback for on-water rowing - Collins, D. J.; Anderson, R.; O'Keeffe, D. T. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
From the results obtained, the possibility of developing a low-cost real-time augmented feedback telemetry communications system for on-water rowing is possible. This would provide a mechanism for rowers, coaches and sport biomechanists to gain valuable biomechanical and kinematical data of a rower's performance as it is occurring. More specifically, as IEEE 802.11 offers a solution regardless of required range or sampling rate. It is on this technology that the developmental drive should be focused as it may offer an all-encompassing solution to both stationary sports (e.g. archery) and ambulatory sports (e.g. rowing). Development of such a real-time augmented feedback system will certainly assist those elite athletes with highly concentrated training programmes.